1976
DOI: 10.1111/j.1749-6632.1976.tb49895.x
|View full text |Cite
|
Sign up to set email alerts
|

Physical Assessment of 30 Chronic Cannabis Users and 30 Matched Controls

Abstract: Ganja is used extensively in the working-class population of Jamaica, particularly in certain agricultural and fishing communities. Ganja, smoking is illegal but can be accepted as part of the culture in these areas. Sixty male subjects were chosen for assessment, 30 chronic smokers and 30 controls from comparable social, economic, and cultural backgrounds, and were matched for height and age. A chronic smoker had somked a minimum of three spliffs per day for a minimum of 10 years. The subjects were admitted t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
8
0

Year Published

1991
1991
2016
2016

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(8 citation statements)
references
References 2 publications
0
8
0
Order By: Relevance
“…The results of these 19 studies are summarised in Table 1 . A total of 11 studies were cross-sectional, 20 , 22–31 and 8 were observational cohort studies. 21 , 32–38 Eighteen out of 19 studies included spirometric measurements in chronic marijuana smokers.…”
Section: Resultsmentioning
confidence: 99%
“…The results of these 19 studies are summarised in Table 1 . A total of 11 studies were cross-sectional, 20 , 22–31 and 8 were observational cohort studies. 21 , 32–38 Eighteen out of 19 studies included spirometric measurements in chronic marijuana smokers.…”
Section: Resultsmentioning
confidence: 99%
“…at the age of 18 years, 2.5% at the age of 21 years, and 5.0% at the age of 26 years compared with nonsmokers (PϽ.05 for all comparisons), but when adjusted for age, tobacco smoking, and weight, the association was no longer statistically significant. Two cross-sectional studies 19,23 reported no differences with respect to FEV 1 / FVC ratio.…”
Section: Long-term Marijuana Smoking and Changes In Pulmonary Functionmentioning
confidence: 95%
“…No difference between marijuana smokers and controls [46] Hernandez et al (1981) Crosssectional 23 Normal spirometry in marijuana smokers [47] Moore et al…”
Section: Crosssectional 60mentioning
confidence: 99%